Affordances & Emergent Language: Teaching at the Point of Need - Gomez, Leo (CIEX JOURNAL, 2025)
What is emergent language, and how can it be effectively used in the classroom? This session explores how affordances and emergent language offer real-time opportunities for learning. Participants will gain practical strategies, a new intervention framework, and insights into how working with EL supports deeper, more personalized language acquisition.